Income Growth and Industrial Landscape: Examining Mexican Household Survey Data - Hoang Linh, Pham; Thuy Linh, Do Thi; Archambault, Steven (VNU Journal of Science: Policy and Management Studies, 2024)
This research explores the economic impact of the existence of industrial sectors throughout communities in Mexico. Of particular interest is the role of maquiladora based industries, or those sectors that import materials and equipment which are then assembled, processed and manufactured into export products. The latest updated data used in the study is from Mexican Family Life Survey managed by Iberoamerican University with other partners. The nationwide household panel data was collected in three waves from 2002 to 2012, with about 8,500 households and 150 communities surveyed. The data is analyzed with the fixed effects regression approach. Results indicate that the presence of maquiladoras in the community has a negative and significant impact on the growth of household income. Of its two parts, the existence of manufacturing facilities has a significantly negative relationship with the growth of household income while assembly plants existence does not have a statistically significant impact. Other variables that indicate robust evidence of importance include the number of people in the household, the number of schools per person in the communities, and the land area per person in the household. Education of the head of household has some positive impacts on household income growth, but the results are not robust